KEBERLANJUTAN KEMITRAAN PETANI PLASMA TEH DAN PT. PAGILARAN : BAGAIMANA DAN APA YANG MEMENGARUHI? - Hani Perwitasari; Arif Wahyu Widada; Anung Pranyoto; Jangkung Handoyo Mulyo; Sugiyarto Sugiyarto; Herdiana Anggrasari (Universitas Sebelas Maret, 2021)
Many Nucleus Estate-Small holding (NES) coo-partnerships often experience dynamics and leave several problems for both parties engaged in the partnership, and in serious way, it may threaten the sustainability of the partnership. This research’s objectives are 1) to determine the level of willingness to sustain the NES coo-partnership, and 2) to analyze the determinant factors of the willingness to sustain the NES coo-partnership. Location of the research comprises two villages namely Kaliboja and Kaliombo, located in Paninggaran sub-district, Pekalongan regency. Ninety tea farmers selected by using convenience sampling method are involved and interviewed. Descriptive method and ordered logistic regression are employed to answer the objectives of the research. The result shows that most farmers are willing to sustain the NES coo-partnership. Moreover, the determinant factors of the willingness to sustain partnerships are the age of farmer, farmer’s tea production, and partnership effectiveness.